The Model of Open Government in Latin America. Parallelism of Public Policies for Transparency and Corruption - Vera Martínez, Martín Cutberto; Rocha Romero, Martín; Martínez Rodríguez, María Concepción (Íconos)
The following article analyzes public policies of administrative reform and related to the institutionalization of access to public information in Mexico, Guatemala and Honduras. It analyzes these policies in relation with the modernization and improvement of public administration and the fight against corruption.